Mengembangkan Produk Olahan Daun Kelor (Studi Kasus UD Herbasina Nutrindo) - Sri Wahyu Vidiya Astutik; Darsan Darsan; Fina Sulistya Ningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Moringa Oleifera (Moringa Oleifera) is a horticultural commodity. In addition to being used as an herbal medicine and being rich in benefits, moringa can also be used as a product diversification ingredient to add value and family income. Therefore, a strategy for business development is needed. This study aims to identify the right strategy to ensure business continuity. To understand the internal and external factors that play a role in business development, namely internal strengths and weaknesses and external opportunities and threats. A total of 37 respondents consisting of internal and external parties were purposively selected to participate in this study. The internal parties included one business owner and four employees directly involved in business management. Meanwhile, the external parties included 30 consumers who were used as informants to provide an overview of the business position from a managerial perspective, as well as one representative from the Head of the Micro Business Trade Office of Bojonegoro Regency, and one representative from the Head of the Ademos Indonesia Partnership located in Dolokgede Village, Tambakrejo District. Based on the Internal Factor Evaluation (IFE) matrix analysis, the main advantage of this business lies in the utilization of high-quality moringa leaves, which have an evaluation score of 0.3064. On the other hand, the External Factor Evaluation (EFE) matrix analysis proves that this business has significant market opportunities, with a total score of 2.908. The results of the SWOT matrix analysis place the business in a maintain and preserve position, which recommends an intensification or diversification strategy. In the context of UD Herbasina Nutrindo, the strategy taken includes market penetration and new product development, optimizing existing advantages to maximize market opportunities. Meanwhile, the Quantitative Strategic Planning Matrix (QSPM) analysis identified that innovation of moringa leaf products is the best alternative strategy, with the highest score of 6.40. This study can determine that developing moringa leaf products is a viable and profitable business for UD Herbasina Nutrindo.